Doxycycline in autoimmune central nervous system disorders in children: an in vitro study - Anlar, Banu; Şenbil, Nesrin; Güven, Alev (The Turkish Journal of Pediatrics, 2007)
Tetracyclines have antiinflammatory properties. To test the in vitro effect of doxycycline in autoimmune neurological disorders of childhood, peripheral blood lymphocytes from multiple sclerosis (n=11), acute disseminated encephalomyelitis (n=12), and control patients (epilepsy and headache, n=12), all aged 5-17, were examined for proliferation, migration, and apoptosis after culture with doxycycline, concanavalin A and myelin basic protein for 48 hours. Doxycycline increased proliferation in the control group, and less in the multiple sclerosis group but not in the acute disseminated encephalomyelitis group (p